Petrogenesis and geological significance of the early Paleozoic S-Type granitic mylonite in the Southwestern Kon Tum Massif, Central Vietnam - Ngo Xuan, Thanh; Luong Quang, Khang; Bui Vinh, Hau; Tran Thanh, Hai; Nguyen Quoc, Hung; Dinh Trong, Tuong (Vietnam Journal of Earth Sciences, 2025)
The Kon Tum Massif (KTM) in central Vietnam represents a key geological component of the Viet-Cam Terrane (VCT), whose early Paleozoic evolution remains poorly constrained, especially along its southwestern margin of the KTM. This study presents new field, petrographic, zircon U-Pb geochronological, and Hf isotopic data, as well as whole-rock geochemical data, from early Paleozoic S-type magmatic rocks in the southwestern KTM, to refine their emplacement age, tectonic setting, and regional geological implications. Zircon U-Pb dating of two samples yields crystallization ages of 445.4±3.5 Ma and 427.5±1.4 Ma, consistent with late Ordovician and early Silurian magmatism. The negative εHf(t) values and rich inherited Paleo- and Neo-Proterozoic zircon indicate a sedimentary-dominated crustal source. At the same time, trace element signatures are characteristic of post-collisional S-type granites. These new findings, in conjunction with a comparable S-type Chu Lai complex in the northern KTM, support a widespread post-collision magmatism during the late Ordovician-Silurian within the KTM. Furthermore, the presence of post-collisional magmatic rocks across the KTM and TSB suggests that the post-collisional tectonic phase had a broad impact on most of the eastern Indochina block during the Late Ordovician-Silurian. This further implies that the collision between the KTM and TSB should have occurred before the late Ordovician.